Next Steps: Adding Site-Level Context, and Pre-Testing Collection of Social Cohesion Metrics - McCarthy, Nancy (2023)
Nancy McCarthy POLICY SEMINAR Research Findings on Resilience & Social Cohesion in Burkina Faso and Niger Co-organized by IFPRI, World Food Programme (WFP), Institute for Peace and Development (IPD), and the CGIAR Research Initiative on Fragility, Conflict, and Migration (FCM) JUL 11, 2023 - 9:00 TO 10:30AM EDT